Representation of Social Criticism of Cyberbullying in Drama 3 Nen A Gumi - Dewi Ayu Putri Budinuljanto Zainul; Dindin Dimyati (Eduvest - Journal of Universal Studies, 2026)
Background: As the rapid growth of digital technology intensified social problems, among them cyberbullying, it has become a very pressing issue in modern society. Objective: This study investigated how 3 Nen A Gumi, a television drama from Japan, depicts and highlights criticism of cyberbullying. Methods: By means of qualitative research within John Fiske's semiotic framework, there were worked out three different levels of codes: reality, representation, and ideology. With regard to the reality level, cyberbullying is indicated through the appearances, behaviors, and emotional expressions of characters. Results: In representation, the means include camera techniques, narrative conflicts, and dialogues. At the ideological level, these show individualism in the drama, where egoism, poor empathy, and weak self-control are highlighted. Conclusion: The findings show that 3 Nen A Gumi condemns not only digital crimes but also broader social issues like youth vulnerability and family disorganization, compounded by the slow response of educational institutions. At last, the drama becomes both entertainment and almost a reflection of society inspiring collective awareness, empathy, and shared responsibility towards cyberbullying.